When we speak [videorecording (DVD)] - Gun, Katharine, 1974-; Evans, Helen (Aid worker); McGowan, Rose, 1973- (Gravitas Ventures, 2022)
British intelligence employee Katharine Gun, Oxfam aid worker Helen Evans and Hollywood actress Rose McGowan open the lid on what happens to women when speaking out against wrongdoing in the documentary.